Unemployed and their caseworkers: should they be friends or foes? - Stefanie Behnke; Markus Frölich; Michael Lechner (Institute for the Study of Labor (IZA), 2007)
In many countries, caseworkers in a public employment office have the dual roles of counselling and monitoring unemployed persons. These roles often conflict with each other leading to important caseworker heterogeneity: Some consider providing services to their clients and satisfying their demands as their primary task. Others may however pursue their strategies even against the will of the unemployed person. They may assign job assignments and labour market programmes without consent of the unemployed person. Based on a very detailed linked jobseeker-caseworker dataset, we investigate the effects of caseworkers' cooperativeness on the employment probabilities of their clients. Modified statistical matching methods reveal that caseworkers who place less emphasis on a cooperative and harmonic relationship with their clients increase their employment chances in the short and medium term.
Keywords: 330; Public employment services; unemployment; statistical matching methods; Arbeitslosigkeit; Arbeitsvermittlung; Arbeitsuche; Verhalten; Motivation; Matching; Schweiz; Arbeitslosigkeit; Arbeitsvermittlung; Arbeitsuche; Verhalten; Motivation; Matching; Schweiz